STUDIES OF BRAHMI BASED UNANI COMPOUND FORMULATION ON AUTISM TO ASSESS ITS EFFICACY - Mukherjee, *Arun; Gupta, Meena; Dogra, Shruti; Sinha, Sumit; Shamsi, Yasmeen (International Journal of Ayurveda and Pharma Research, 2017)
Autism is most common neurodevelopmental disorder seen in pediatric population. The ratio of autism spectrum disorder now a days increasing day by day according to Indian statistical data. In autism child generally have poor socialization, communication and speech issue which is normal in few months of the age and start regress in second years of life. In field of rehabilitation autism has better results by occupational therapy, speech therapy and early intervention. In this study we tried the Centella asiatica extract in form of Brahmi to treat many clinical symptoms such as cognition, poor attention span, hyperactivity, not responding name in autistic children. The outcome measure Childhood Autism Rating Scale and Vineland Social Maturity Scale were used for pre and post test assessment and after the statistical analysis the result suggested that experimental group have more significance result that is p< 0.01 in experimental group than control group that is p<0.09. It also suggested that score of CARS and VSMS show maximum change by employing Brahmi with other rehabilitation intervention in autistic kids.